A micro‐computed tomographic evaluation of retreatability of BioRoot RCS in comparison with AH Plus. (29th October 2020) - Alsubait, Sara; Alhathlol, Nuha; Alqedairi, Abdullah; Alfawaz, Hussam
Abstract: This study compared the retreatability of filling material from canals filled with BioRoot RCS (Septodont, Saint‐Maur‐des‐Fosses, France) and AH Plus (Dentsply DeTrey, Konstanz, Germany) combined with gutta‐percha using micro‐computed tomography for evaluation. Thirty‐four mandibular premolars were divided into two groups according to the sealer used. Thirty days after obturation, canals were retreated with a ProTaper Universal retreatment system (Dentsply Maillefer, Ballaigues, Switzerland) followed by passive ultrasonic irrigation (PUI). The time taken for retreatment was recorded. The roots were scanned after obturation, after retreatment and after PUI. Data were analysed using the Mann–Whitney and Wilcoxon tests. Canals filled with BioRoot RCS exhibited significantly less remaining filling material than canals filled with AH Plus ( P  < 0.05). The addition of PUI resulted in a significant decrease in the residual material in both groups ( P  < 0.05). A significantly shorter retreatment time was reported for the AH Plus group than the BioRoot RCS group ( P  < 0.05).